First-principles calculations on electronic properties of LaNiO3 in solid oxide fuel cell cathodes - Pham Ba, Duy; Nguyen, Huy Duy; Bach, Cong Thanh (VNU Journal of Science: Mathematics - Physics, 2017)
First-principles calculations based on the density functional theory are used to study the electronic structure of LaNiO 3 perovskite for application of cathode material in solid oxide fuel cell. Our results show that bulk LaNiO 3 exhibits metallic behavior. For 1x1x1 LaNiO 3 unit cell, increasing in-plane strain leads to the increase in the density of states (DOS) at the Fermi level. On the other hand, the DOS at the Fermi level for 2x2x2 LaNiO 3 supercell first increases with the strain up to 3% and then decreases for larger values of the strain. The difference between the electronic structure of the 2x2x2 supercell and that of the 1x1x1 unit cell is attributed to the rotations of NiO 6 octahedra.